PSYCHOLOGICAL ASPECTS OF THE MANIFESTATION OF DEFICIT MOTIVES (British Journal of Global Ecology and Sustainable Development, 2024)
This article presents the originality, psychological essence and basics of the phenomenon of deficit motives. Studies of foreign approaches to the motives of deficit are revealed. Psychological factors influencing the motives of deficiency were also analyzed.